Mequindox-Induced Kidney Toxicity Is Associated With Oxidative Stress and Apoptosis in the Mouse - Liu, Qianying; Lei, Zhixin; Guo, Jingchao; Liu, Aimei; Lu, Qirong; Fatima, Zainab; Khaliq, Haseeb; Shabbir, Muhammad A B; Maan, Muhammad Kashif; Wu, Qinghua; Dai, Menghong; Wang, Xu; et al. (Frontiers in pharmacology, 2018)
Mequindox (MEQ), belonging to quinoxaline-di-N-oxides (QdNOs), is a synthetic antimicrobial agent widely used in China. Previous studies found that the kidney was one of the main toxic target organs of the QdNOs. However, the mechanisms underlying the kidney toxicity caused by QdNOs in vivo still remains unclear. The present study aimed to explore the molecular mechanism of kidney toxicity in mice after chronic exposure to MEQ. MEQ led to the oxidative stress, apoptosis, and mitochondrial damage in the kidney of mice. Meanwhile, MEQ upregulated Bax/Bcl-2 ratio, disrupted mitochondrial permeability transition pores, caused cytochrome c release, and a cascade activation of caspase, eventually induced apoptosis. The oxidative stress mediated by MEQ might led to mitochondria damage and apoptosis in a mitochondrial-dependent apoptotic pathway. Furthermore, upregulation of the Nrf2-Keap1 signaling pathway was also observed. Our findings revealed that the oxidative stress, mitochondrial dysfunction, and the Nrf2-Keap1 signaling pathway were associated with the kidney apoptosis induced by MEQ in vivo.
Keywords: quinoxaline-di-N-oxides; Nrf2-Keap1; oxidative stress; mequindox; apoptosis